Vegetation description of representative habitat complexes along the Maros (Mureş) river - Margóczi Katalin; Drâgulescu Constantin; Macalik K.; Makra O. (2002)
Detailed identification and description of still existing natural or semi natural habitat complexes is necessary to planning conservation strategics, or restoration programs of deteriorated riverside habitats. The Maros River with its 768-km length is the most important tributary of the Tisa River. Since 1991 Hungarian and Rumanian non-governmental organisations has started interdisciplinary research to assess the common river's environmental condition. On the base of this pilot research 4 representative and highly natural areas has been selected for more detailed scientific investigations: (1) peat bog at Vasläb/Vo?lobeni in Giurgcu (Gyergyoi) basin, (2) lower Mure§/Maros pass between Ilia and Deva, (3) Pecska/Pecica-Bezdin forest, (4) Maros section in Hungary. Cenological relcves were made in 5-6 representative and natural or semi natural vegetation stands. A description and comparative evaluation of the river valley vegetation were made on the base of these relcves.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok; Biológiai tudományok